Microbial population dynamics during sludge granulation in an A/O/A sequencing batch reactor. (August 2016) - He, Qiulai; Zhou, Jun; Wang, Hongyu; Zhang, Jing; Wei, Li
Highlights: Granulation was realized at an organic loading rate as low as 0.3 kg COD/(m 3 ·d). Simultaneous COD, nitrogen and phosphorus removal were achieved over operation. Bacterial population dynamics were explored by MiSeq pyrosequencing. Dominant functional groups for granulation and pollutants removal were identified. Abstract: The evolution of the bacterial population during formation of denitrifying phosphorus removal granular sludge was investigated using high-throughput pyrosequencing. As a result, mature granules with a compact structure were obtained in an anaerobic/aerobic/anoxic (A/O/A) sequencing batch reactor under an organic loading rate as low as 0.3 kg COD/(m 3 ·d). Rod-shaped microbes were observed to cover with the outer surface of granules. Besides, reliable COD and simultaneous nitrogen and phosphorus removal efficiencies were achieved over the whole operation period. MiSeq pyrosequencing analysis illustrated that both the microbial diversity and richness increased sharply during the granulation process, whereas they stayed stable after the presence of granules. Some microorganisms seemed to contribute to the formation of granules, and some were identified as functional bacterial groups responsible for constructing the biological reactor.